Innovative refractance window drying technology to keep nutrient value during processing. (February 2019) - Bernaert, Nathalie; Van Droogenbroeck, Bart; Van Pamel, Els; De Ruyck, Hendrik
Abstract: The evaluation of the impact of food processing on the nutrients and health benefits of vegetables and fruits is of high practical importance. In this short literature overview the refractance window drying (RWD) technology, a novel contact drying technique, was compared with other drying techniques as the freeze drying technique to stabilize fruits and vegetables. The antioxidant capacity, phenolic or polyphenol content and carotenoids are important published quality properties. The RWD technology as mild drying process showed various opportunities to maintain the product quality and the nutrient content as well as their biological activity to a high degree. Highlights: Refractance window drying (RWD) technology is a mild drying process. Air-drying, freeze drying and RWD retained almost the same antioxidant capacity in leek samples. The antioxidant capacity of RW dried fruit is significantly higher than in spray-dried samples. The energy efficiency of the RW dryer is 3-fold and 40-fold higher compared to the spray dryer and the freeze dryer, respectively. The content of carotenoids and capsaicinoids decreases significantly by freeze drying and oven drying as well as RW drying.